2014
DOI: 10.1038/ncomms6117
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analyses uncover origin and spread of the Wolbachia pandemic

Abstract: Of all obligate intracellular bacteria, Wolbachia is probably the most common. In general, Wolbachia are either widespread, opportunistic reproductive parasites of arthropods or essential mutualists in a single group of filarial nematodes, including many species of medical significance. To date, a robust phylogenetic backbone of Wolbachia is lacking and consequently, many Wolbachia-related phenomena cannot be discussed in a broader evolutionary context. Here we present the first comprehensive phylogenomic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
126
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(140 citation statements)
references
References 71 publications
12
126
1
Order By: Relevance
“…wDacA was resolved as the most phylogenetically distant strain within supergroup A, whereas wDacB was a member of supergroup B having wVitB from Nasonia vitripennis as its closest sequenced relative. The strain wFol associated with the springtail Folsomia candida was found placed as the most distant of all the analyzed Wolbachia supergroups as reported previously [36].…”
Section: Genome-based Relationshipssupporting
confidence: 57%
See 1 more Smart Citation
“…wDacA was resolved as the most phylogenetically distant strain within supergroup A, whereas wDacB was a member of supergroup B having wVitB from Nasonia vitripennis as its closest sequenced relative. The strain wFol associated with the springtail Folsomia candida was found placed as the most distant of all the analyzed Wolbachia supergroups as reported previously [36].…”
Section: Genome-based Relationshipssupporting
confidence: 57%
“…For G + C content determination, contigs of each genome were concatenated, the number of G plus C nucleotides counted and the sum divided by the genome length. Genome of strain wMen was obtained from the Strepsiptera Genome Project [68], and genomes of strains wFol, wOc and wCte were only deposited like Sequence Read Archive (SRA) so they were not included in G + C determination because they were not completely sequenced [36].…”
Section: Genome Sequencesmentioning
confidence: 99%
“…Moreover, interaction between Wolbachia of supergroup E and its host may be a form of evolved dependence. The role of strains of supergroup H remains unresolved (Gerth et al, 2014). In our research with the maximum-likelihood method, analysis of gene sequences downloaded from GenBank as comparative material revealed that Wolbachia of supergroup A from Ephestia kuehniella formed a clade with bacteria of supergroup B and another clade was formed by a strain of supergroup M from Aphis fabae with bacteria of supergroup A.…”
Section: Discussionmentioning
confidence: 96%
“…– Pseudogenes or Wolbachia infections: both are common in invertebrates, particularly in arthropods (Bensasson et al 2011, Gerth et al 2014, Leite 2012, Ritter et al 2013). As the vast majority of the haplotypes in the ‘ mamurra ’ and ‘ pelopea ’ clades originate from the BOLD database it is impossible to check or correct for this potential error.…”
Section: Discussionmentioning
confidence: 99%